Caracterização ambiental da paisagem da microrregião colonial de Irati e zoneamento ambiental da Floresta Nacional de Irati, PR - Mazza, Carlos Alberto da Silva (Universidade Federal de São Carlos, 2006)
The protected areas are the most effective places for in situ conservation of biological diversity. These areas must occupy a land extension that tends to maximize the ecosystems integrity and the representativeness of the ecological communities and of its component species. It must also reduce to a minimum the risks of species extinction. In Brazil, these areas were established for the first time in 1937, with the creation of Itatiaia National Park. From then, several protected areas were established in the country and, among them, the Irati National Forest Irati Flona, a federal area, category of Sustainable Use. The Flona has 3,618 ha containing remnants of the Mixed Ombrophylous Forest (Araucaria Forest) in different successional stages. Presently, the region where Irati Flona is localized has two other protected areas, the Fernandes Pinheiro Ecological Station and the Araucaria Biological Park. These three protected areas are adjacent and, together, represent 19,070 ha and form an important mosaic of remnants, aiming at protecting the Mixed Ombrophylous Forest in the Center-south of Parana State. The characterization and analysis of the structure of Irati Flona landscape and of the four municipalities around, as the conceptual proposal for environmental zoning were established in a Geographical Information System, so as to make a georeferred digital database that allow the handling and analysis of the data. The steps for zoning establishment started with the history of colonization and occupation, in order to understand the occupation dynamics of the original landscape until reaching the actual conformation. The following steps used the topographic, geological and soil maps, as well as satellite and radar images, which allowed to establish the necessary thematic maps, used to analyze the biophysical aspect of the region and identify the factors that threaten the integrity of the biological diversity of Flona, and to present a proposal for an environmental conceptual zoning. Based on the characterizations and analyses that were done, it was possible to identify ...
Keywords: Ecologia; Ecologia da paisagem; Zoneamento ambiental; Unidades de conservação, Planejamento ambiental; Sistemas de informação geográfica; CIENCIAS BIOLOGICAS::ECOLOGIA